Interdisciplinary Approach to Healthcare Quality Improvement: Integrating Clinical, Administrative, and Informatics Perspectives - Maha Msfer Alasmari, Faten Hamed Alanzi, Abdulrahman Muayjil Almutairi, Ayed Shabeb Almutairi, Mashary Fahad Alhmdane, ‏Raed Lafi Almutairi, ‏Adel Saad Almutairi; Saeed Saud Murayziq Almutairi, Mamdouh Shalh Moateq Al-Mutairi, Norah Mohammed Hazazi, Shatha Abdullah Aldailej, Fatimah abbas Alsada (Journal of International Crisis and Risk Communication Research, 2024)
Delivering high-quality healthcare requires an interdisciplinary approach that integrates the perspectives and expertise of various professionals across clinical, administrative, and informatics domains. This paper explores the significance of interdisciplinary collaboration in healthcare quality improvement, highlighting the roles and contributions of diverse professionals, including physicians, nurses, allied health practitioners, administrators, quality improvement specialists, health informaticians, and data analysts. It examines the challenges associated with interdisciplinary teamwork, such as professional silos, role ambiguity, communication barriers, limited interprofessional education, and resource constraints. Strategies for effective collaboration are discussed, including shared decision-making processes, data-driven quality improvement, continuous feedback and evaluation, and interprofessional education. The integration of clinical, administrative, and informatics perspectives is showcased through examples from various healthcare settings, including inpatient, outpatient, palliative care, chronic disease management, pediatric care, and geriatric care. By embracing an interdisciplinary approach and fostering a culture of teamwork, healthcare organizations can enhance patient outcomes, optimize resource utilization, drive innovation, and ultimately achieve the quadruple aim of better population health, improved patient experience, reduced costs, and support for healthcare provider well-being.